ANALISIS PERBANDINGAN WAKTU DAN BIAYA KONSTRUKSI BETON MENGGUNAKAN METODE CETAK DITEMPAT DAN PRACETAK - Fitri Awaliah; Siti Nurasiyah; Istiqomah Istiqomah (Kokoh, 2021)
The selection of a construction method can result in differences in cost and time in its implementation. The wiser we are in choosing a construction method, then we will get the best results, especially in terms of cost and time. In the implementation of concrete work there are several methods including the on-site molding method and precast.Keywords: Cast- In Situ Concrete, Cost Analysis, Implementation, Precast Concrete, , Time Analysis